ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP INTERNAL SERVICE QUALITY (STUDI KASUS DI PT. ASA YOGYAKARTA) - Lucia Yemi Dinaria; Endah Utami (Universitas Ahmad Dahlan, 2011)
This study revolves about the Internal Service Quality in PT. ASA Yogyakarta engaged in the production of golf gloves. In the face of strict quality requirements in global markets, the management of PT. ASA Yogyakarta expected to be able to create a high quality product that can meet the needs and desires of its customers, and provides high customer satisfaction. In an attempt to give the best quality to the consumer role of internal service quality is very important and strategic, this is due to embody the role of quality starts from the internal customer. This study aims to analyze the effect of internal service quality, leadership, customer orientation, organizational commitment, and job satisfaction of internal service quality. The results of this research is based on an assessment of the employee survey results that the internal communication, leadership, customer orientation, organizational commitment and customer satisfaction are silmutan significant effect on internal service quality. This suggests that the good and bad internal service quality in Yogyakarta, 94% PT ASA is determined by the internal communication, leadership, customer orientation, organizational commitment and job satisfaction. While the rest are caused by other variables not included in this study.